Contribution of tryptophan and its metabolites to transplant outcome: a mini-review - Donoso-Meneses, Darío; Padilla, Cristina; Moya-Guzmán, María José; Alegre, Maria-Luisa; Pino-Lagos, Karina (Frontiers in Immunology, 2024)
Long-term tolerance in the absence of immunosuppressive drugs is a major goal in the transplantation field, not yet attained. Recent research on the role of commensal microbiota in the control of immunity has opened new avenues for the search of novel clinical interventions.Indeed, products of intestinal metabolism generated by both host cells and the microbiota have been identified as modulators of the immune response. Among these, tryptophan (Trp) and its derivatives are being investigated to understand their impact on alloimmunity and their potential usefulness as therapeutic targets to improve allograft survival. Here, we reviewed the latest findings on the contribution of Trp metabolic pathways to transplant outcomes.